Characterization and classification of soils hydromorphic about mudslides fluvio-marine the municipality of arari - Ma - Filho, Marcelino Silva Farias; Bueno, Célia Regina Paes [UNESP]; Valladares, Gustavo Souza (Universidade Federal do Paraná, 2020)
The Baixada Maranhense, a microregion influenced by the Golfão Maranhense, presents pedogenetic conditions that are associated with the depositional fluvial and marine mechanisms, typical of the Fluviomarine alluvies in the central portion of the Maranhão coast, which allows the dominant occurrence of hydromorphic soils, such as the Gleissolos. The intensification of agricultural use requires that the different characteristics of hydromorphic soils be known and taken into account when using them, since countless families depend on the use of these soils to guarantee food and income. The objective of this work was to characterize and classify the soils cultivated with irrigated rice and used with extensive livestock, which are on sedimentary material from the fluvial and marines alluvies, in the municipality of Arari, Maranhão. Field work was carried out to characterize the environment and the different forms of land use and two trenches were opened at different points, one in an area with integrated irrigated rice cultivation and extensive livestock in the last six years and another in an area used only with livestock extensive in native vegetation. Soils were analyzed for morphology, granulometry (sand, silt and clay), assortment complex (Ca2 +, Mg2 +, Na +, K + and Al3 +), S, potential acidity (H + Al), assimilable P, pH (water and KCl) and sulfuric attack (oxides of Fe, Al and Si). In both profiles, the soils were classified, according to the Brazilian Soil Classification System, as typical Allytic Melanic Gleysol, very clayey texture, A prominent. They have a low degree of pedogenetic development, with high-activity clay fraction minerals associated with the marked presence of kaolinite, which gives them high CTC and low values for V% and several limitations to uses.
Caracterização e classificação de solos hidromórficos sobre os aluviões fluviomarinhos no município de arari - Ma
Keywords: Kaolinite; Melanic gleisol alitic typical; Pedogenesis